Intraocular Foreign Bodies: Clinical Characteristics and Prognostic Factors Influencing Visual Outcome and Globe Survival in 373 Eyes - Yang Liu; Shuang Wang; Ying Li; Qiaoyun Gong; Guanfang Su; Jinsong Zhao (Journal of Ophthalmology)
Aim. To describe epidemiologic and clinical characteristics and prognostic factors influencing visual outcome after intraocular foreign bodies (IOFBs) injury. Methods. Medical records of 370 patients (373 eyes) with IOFBs were reviewed to identify the factors influencing visual acuity by univariate and multivariate analyses. Results. The majority of patients (97.0%) were men, with a mean age of 38.1 years. The most common cause of ocular injury was hammering (52.6%); magnetic IOFBs occurred in 84.7% of these cases. Factors associated with poor visual outcome (defined as <1.3 logMAR) included the following: age ≥50 years (P=0.046); worse presenting visual acuity (P<0.001); complications of retinal breaks (P=0.006) and endophthalmitis (P=0.032); vitrectomy (P=0.035); and intraocular C3F8 gas tamponade (P=0.038). Excellent visual outcome (defined as ≥0.5 logMAR) was associated with age <50 years (P=0.003); better presenting visual acuity (PVA) (P<0.001); wound length <4 mm (P=0.005); absence of vitreous hemorrhage (P=0.026) and retinal breaks (P<0.001); nonvitrectomy surgery (P=0.043); and use of balanced saline (P=0.029). Conclusions. Multiple prognostic factors were identified that may predict visual outcome and globe survival after IOFBs injury. Age, initial presenting visual acuity, wound length, complications (vitreous hemorrhage, retinal breaks, and endophthalmitis), surgical approach, and intraocular tamponade were significant predictors of visual outcome.